(130) Treatment of the public administration sector in input -output معاملة قطاع الإدارة العامة في المدخلات والمخرجات - N.DAIF (معهد التخطيط القومي, 2026)
تتناول المذكرة إشكالية معالجة قطاع الإدارة العامة في جداول "المدخلات والمخرجات" (Input-Output)، حيث يستعرض الدكتور نظمي ديف الصعوبات المفاهيمية والإحصائية المرتبطة بقياس مخرجات هذا القطاع وتأثيراتها في الاقتصاد الوطني. يشدد البحث على ضرورة عدم الاعتماد الكلي على النماذج الرياضية الآلية أو تجارب الدول الأخرى بشكل أعمى، داعياً إلى دراسة كل وظيفة إدارية كشأن مستقل خاصة عند التخطيط لنمو اقتصادي سريع، كما يوثق الملف تطور التجربة المصرية في التخطيط القومي، موضحاً التحول من استخدام مصفوفات "ليونتييف" البسيطة في عام 1957 إلى تبني جداول مدخلات ومخرجات عامة أكثر مرونة وتفصيلاً تشمل مئات السلع. ويؤكد الكاتب أن هذا التطور ساعد في فحص خطط الوزارات وتنسيق الإنفاق الحكومي بشكل أكثر دقة، رغم التحديات التي واجهت التنبؤ بنفقات الاستثمار في البداية، معتبراً أن الجداول العامة توفر نتائج أكثر إقناعاً في عملية موازنة الموارد والاستخدامات على المستوى القومي. The memorandum addresses the challenges of analyzing the public administration sector using input-output tables. Dr. Nazmi Deif reviews the conceptual and statistical difficulties associated with measuring the outputs of this sector and their impact on the national economy. The research emphasizes the need to avoid relying solely on automated mathematical models or blindly adopting the experiences of other countries. It calls for studying each administrative function as an independent entity, especially when planning for rapid economic growth. The document also chronicles the evolution of the Egyptian national planning experience, illustrating the shift from using simple Leontief matrices in 1957 to adopting more flexible and detailed general input-output tables encompassing hundreds of goods. The author asserts that this development facilitated a more precise examination of ministerial plans and coordination of government spending, despite the initial challenges in forecasting investment expenditures. He argues that general tables provide more convincing results in the process of balancing resources and expenditures at the national level.